Reasons and reproduction: gene editing and genetic selection - McMahan, J; Savulescu, J (Taylor & Francis, 2023)
Many writers in bioethics, science, and medicine contend that embryo selection is a morally better way of avoiding genetic disorders then gene editing, as the latter has risks that the former does not. We argue that one reason to use gene editing is that in many cases it would be better for the person who would develop from the edited embryo, so that not to have done it would have been worse for that person. By contrast, embryo selection is never better for the person who develops from the selected embryo. This reason to use gene editing has, however, been challenged on two grounds: first, that it makes no difference, morally, whether a bad effect is worse for someone, or a good effect better for someone; and, second, that beneficent gene editing would not be unequivocally better for the person who would develop from the edited embryo. We argue that both of these objections can be satisfactorily answered and thus that there is indeed a significant moral reason, at least in some cases, to use gene editing rather than embryo selection.